Biomedical engineering of polysaccharide-based tissue adhesives: Recent advances and future direction. (1st November 2022) - Shokrani, Hanieh; Shokrani, Amirhossein; Seidi, Farzad; Munir, Muhammad Tajammal; Rabiee, Navid; Fatahi, Yousef; Kucinska-Lipka, Justyna; Saeb, Mohammad Reza
Abstract: Tissue adhesives have been widely used for preventing wound leaks, sever bleeding, as well as for enhancing drug delivery and biosensing. However, only a few among suggested platforms cover the circumstances required for high-adhesion strength and biocompatibility, without toxicity. Antibacterial properties, controllable degradation, encapsulation capacity, detectability by image-guided procedures and affordable price are also centered to on-demand tissue adhesives. Herein we overview the history of tissue adhesives, different types of polysaccharide-based tissue adhesives, their mechanism of gluing, and different applications of polysaccharide-based tissue adhesives. We also highlight the latest progresses in engineering of tissue adhesives followed by existing challenges in fabrication processes. We argue that future studies have to place focus on a holistic understanding of biomaterials and tissue surface properties, proper fabrication procedures, and development of magnetic and conductive responsive adhesives in order to bridge the huge gap between the present studies for clinical implementation. Graphical abstract: Unlabelled Image